# Solve `-3/(1-2x) = 4/(x-3)` .can you show step by step i just got so confused

*print*Print*list*Cite

Expert Answers

lemjay | Certified Educator

`-3/(1-2x)=4/(x-3)`

To solve rational equations, we need to eliminate the denominators. To do so, multiply both sides by the LCD.

`-3/(1-2x)*(1-2x)(x-3)=4/(x-3)*(1-2x)(x-3)`

`-3(x-3)=4(1-2x)`

`-3x+9=4-8x`

Then, combine like terms. So move the terms with x on one side of the equation. While the constants on the other side of the equation.

`-3x + 9 = 4 - 8x`

`+3x - 4` `-4 + 3x`

`------------`

`0 + 5 = 0 - 5x`

`5 = -5x`

And isolate x by dividing both sides by -5.

`5/(-5)=(-5x)/(-5)`

`-1=x`

**Answer: `x =-1` **

Student Comments

vaaruni | Student

Given :
-3/(1-2x) = 4/(x-3)
=>{-3/(1-2x)}*(1-2x)={4/(x-3)}*(1-2x)[ multiplying both side
by (1-2x) ]
=>(-3)=(4(1-2x))/(x-3)
=>(-3)*(x-3)={(4*(1-2x))/(x-3)}*(x-3)[ multiplying both side
by (x-3) ]
=> -3(x-3)=4(1-2x)
=> -3x+9 = 4-8x
=> -3x+8x+9 = 4-8x+8x [ adding both side 8x]
=> 5x+9 = 4
=> 5x+9-9 = 4-9 [subtracting both side 9]
=> 5x = -5
=> x = (-5)/5 = -1
Hence x = -1 <--Answer